Effect of Material Structure on Photoluminescence of ZnO/MgO Core‐Shell Nanowires. Issue 3 (19th January 2018) - Marvinney, Claire E.; Shen, Xiao; McBride, James R.; Critchlow, Dominic; Li, Zhineng; Mayo, Daniel C.; Mu, Richard R.; Pantelides, Sokrates T.; Haglund, Richard F.
Abstract: Zinc oxide (ZnO) nanowires are widely studied for use in ultraviolet optoelectronic devices, such as nanolasers and sensors. Nanowires (NWs) with an MgO shell exhibit enhanced band‐edge photoluminescence (PL), a result previously attributed to passivation of ZnO defects. However, we find that processing the ZnO NWs under low oxygen partial pressure leads to an MgO‐thickness‐dependent PL enhancement owing to the formation of optical cavity modes. Conversely, processing under higher oxygen partial pressure leads to NWs that support neither mode formation nor band‐edge PL enhancement. High‐resolution electron microscopy and density‐functional calculations implicate the ZnO m‐ plane surface morphology as the key determinant of core‐shell structure and cavity‐mode optics. A ZnO surface with atomic steps along the m‐ plane in the c‐ axis direction stimulates the growth of a smooth MgO shell that supports guided‐wave optical modes and enhanced UV PL. On the other hand, a smoother ZnO surface leads to nucleation of a rough cladding layer which supports neither enhanced UV PL nor optical cavity modes. Finite‐element analysis shows a clear correlation between allowed Fabry‐Perot and whispering gallery modes and enhanced UV‐PL. These results point the way to fabricating ZnO/MgO core‐shell nanowires for more efficient UV nanolasers, scintillators, and sensors. Abstract : Core‐shell nanowires : Zinc‐oxide/magnesium‐oxide core‐shell nanowires exhibit an enhanced band‐edge photoluminescence that depends on shell thickness. Wave‐guided optical cavity modes are found to contribute more significantly to ZnO band‐edge photoluminescence enhancement than ZnO defect passivation. Surprisingly, this mode‐driven enhancement is so sensitive to the ZnO and MgO material processing conditions and interface structure that it can be completely quenched.